Tata the global corporation that built Indian capitalism - Raianu, Mircea, 1987- (Harvard University Press, 2021)
"Tata is one of the world's most diversified companies, selling everything from salt to software. Mircea Raianu charts Tata's 150-year trajectory, through the eras of imperial free trade, protectionist nationalism, and market liberalization and asks what the future has in store for India's leading brand and for capitalism writ large"--